Gal-3 y ST2 como biomarcadores: un paso al frente en el pronóstico de la Insuficiencia Cardíaca - Mário Barbosa; Andreia Matos; Manuel Bicho (Sociedade Galega de Medicina Interna, 2000)
Abstract Aims The American College of Cardiology (ACA)/ American Heart Association (AHA) granted Galectin-3 (Gal-3) and Suppression of Tumorigenicity 2 (ST2) evaluation a class II recommendation for HF prognosis, as an adjunctive to conventional clinical risk factors and natriuretic peptides dosing in 2013. However, in Europe this endorsement is not valid. The purpose of this study was to study the association of Gal-3 and ST2 collected at-admission with early (defined as the period of 90 days post-discharge) rehospitalization and overall mortality, and end of follow-up overall mortality in HF patients. Additionally, aminoterminal B-type natriuretic peptide (NT-proBNP) at-admission was considered to test if a multi-marker strategy could yield supplementary information. Material and Methods Gal-3, ST2 and NT-proBNP were assessed in patients hospitalized with acute decompensated HF in class III or IV of New York Heart Association (NYHA). Univariate Cox proportional hazard model was used to assess the relationship between variables and outcomes. Since there are no standardized cut-offs for Gal-3 and ST2, the multiclass Area Under the Curve Receiver-Operator Characteristic (AUCROC) as defined by Hand and Till was used to evaluate the overall performance of each biomarker as a predictor of the outcomes. Results We followed 65 patients for a median of 13.7 (Q1-Q3 6.7-18.9) months. Gal-3 correlated with short-term rehospitalization (HR: 9.886, 95% CI: 2.027-48.214, P-value=0.005), short-term mortality (HR: 13.731, 95% CI: 1.650-114.276, P value=0.015) and end of follow-up mortality (HR: 4.492, 95% CI: 1.594-12.656, P-value=0.004). The association of elevated NT-proBNP determinations increased the risk of short-term rehospitalization (HR: 11.985, 95% CI: 1.962-73.218, P value=0.007) and end of follow-up mortality (HR: 78.025, 95% CI: 7.592-801.926, P-value<0.001). ST2 correlated with end of follow-up mortality (HR: 4.846, 95% CI: 1.396-16.825, P-value=0.013). The risk further increased if NT-proBNP (HR: 5.953, 95% CI: 1.683-21.055, P-value=0.006) or Gal-3 determinations (HR: 6.209, 95% CI: 2.393-16.114, P-value<0.001) were added. Conclusions Elevated Gal-3 concentrations correlated with short-term rehospitalization, short-term mortality and end of follow-up mortality; whereas ST2 prognosticated end of follow-up mortality. Collective analysis with elevated NT-proBNP values further increased the outcomes' risk. These results corroborate the assumption that promising novel biomarkers Gal-3 and ST2 could be valuable for HF risk stratification. We highlight that a multi-marker strategy added information, as a synergism between myocardial fibrosis biomarkers and the myocardial stretch peptide was observed.